Complete genome and transcriptomes of Streptococcus parasanguinis FW213: phylogenic relations and potential virulence mechanisms. - Jianing Geng (Public Library of Science (PLoS), 2012)
Streptococcus parasanguinis, a primary colonizer of the tooth surface, is also an opportunistic pathogen for subacute endocarditis. The complete genome of strain FW213 was determined using the traditional shotgun sequencing approach and further refined by the transcriptomes of cells in early exponential and early stationary growth phases in this study. The transcriptomes also discovered 10 transcripts encoding known hypothetical proteins, one pseudogene, five transcripts matched to the Rfam and additional 87 putative small RNAs within the intergenic regions defined by the GLIMMER analysis. The genome contains five acquired genomic islands (GIs) encoding proteins which potentially contribute to the overall pathogenic capacity and fitness of this microbe. The differential expression of the GIs and various open reading frames outside the GIs at the two growth phases suggested that FW213 possess a range of mechanisms to avoid host immune clearance, to colonize host tissues, to survive within oral biofilms and to overcome various environmental insults. Furthermore, the comparative genome analysis of five S. parasanguinis strains indicates that albeit S. parasanguinis strains are highly conserved, variations in the genome content exist. These variations may reflect differences in pathogenic potential between the strains.